SIMILARITIES AND DIFFERENCES THE CATEGORIES OF NUMBER AND PERSON WHICH IS GRAMMATICAL CATEGORIES OF NOUN IN ENGLISH AND UZBEK LANGUAGES - Navruza Karimova; Aziz Mukhamadiev (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article analyzes the grammatical categories of number and person in English and Uzbek languages, specifically within the context of nouns. It elucidates the similarities and differences in their expression and utilization in constructing sentences through illustrative examples and explanations. This article seeks to explore the perspectives of both English and Uzbek scholars on this linguistic phenomenon. Through an examination of relevant theories and examples from English and Uzbek literature, we aim to compare and contrast the terminologies and approaches employed in each language.